1980
DOI: 10.1084/jem.151.5.1232
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte cooperation is required for amplification of macrophage procoagulant activity.

Abstract: Murine splenic lymphoid cells have been shown to possess basal procoagulant activity. This activity was localized to most macrophages by assay of cell populations, as well as by a direct plaque assay that permitted identification of expressed procoagulant activity of individual viable cells as well as content. Both content and viable expression of procoagulant activity was markedly increased by exposure to bacterial lipopolysaccharide, reaching a maximum after 6 h. The quantitative increase in procoagulant act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
104
2

Year Published

1981
1981
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(116 citation statements)
references
References 25 publications
10
104
2
Order By: Relevance
“…T lymphocytes have been proposed as modulators of TFa, since they can enhance the effect of certain stimuli (5). Some investigators have suggested that the requirement for T lymphocytes in the induction ofTFa is absolute (12).…”
Section: Introductionmentioning
confidence: 99%
“…T lymphocytes have been proposed as modulators of TFa, since they can enhance the effect of certain stimuli (5). Some investigators have suggested that the requirement for T lymphocytes in the induction ofTFa is absolute (12).…”
Section: Introductionmentioning
confidence: 99%
“…We estimate the mean Factor VII associated with the cells of sarcoid patients to be 4.7 ng/10' cells (range 0. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] (1,2). Attenuation of the hypercellular characteristics of acute complex glomerulonephritis by antimacrophage antiserum (3) and by defibrinogenation (4) indicated a direct causal role for both the macrophage and fibrin in immunologically mediated tissue injury.…”
mentioning
confidence: 99%
“…This reveals that the PCA-releasing potential of alveolar macrophages is influenced by lymphocytes, and that lymphocyte co-operation seems necessary for the increased PCA production. It has been shown that T-lymphocytes [23] and T-lymphocyte factors [31] are important for the increased production of PCA by the monocytes and macrophages. Further, the monocyte procoagulant-inducing factor (MPIF) has been shown to be a T-helper cell derived cytokine, that may play a collaborative role in the expression of cell-mediated immune responses [32].…”
Section: Discussionmentioning
confidence: 99%
“…The adherent mononuclear cells (monocytes -nonspecific esterase positive cells) and the alveolar macrophages were cultured for 72 h at 37°C, either with or without purified protein derivative (PPD) of M. tuberculosis (Central Veterinary Laboratory, Weybridge, Surrey, UK). In the second set of experiments 1×10 6 cells·ml -1 alveolar macrophages were co-cultured with 4×10 6 cells·ml -1 autologous lymphocytes (1:4 ratio) [23]. In the third set of experiments, 1×10 6 cells·ml -1 alveolar macrophages and 4×10 6 cells·ml -1 autologous lymphocytes were cocultured with 20 µg·ml -1 of PPD.…”
Section: Design Of the Experimentsmentioning
confidence: 99%